Inserç\~ao no mercado internacional e a produç\~ao de carnes no Brasil - Marcelo Dias Paes Ferreira; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This work aimed to synthetize information regarding beef, pork and broiler production in Brazil, as well as the role of Brazil in the international market. This study was developed within a partnership between The Brazilian Trade and Investment Promotion Agency (Apex-Brasil) and The Institute for Applied Economic Research (Ipea). We find that both production and productivity have increased from 2009 to 2018. These increments allowed Brazil to be a major player in meat production and exports during the period, which is strongly related to cost advantages over other countries. China has increased its meat imports from Brazil, whilst Russia systematically reduced its beef and pork. Overall, we suggest to policymakers to set up strategies to promote Brazilian meat and open new markets in order to diversify the consumers and reduce the exports dependence, and its inherent risks, to few countries.
Keywords: Q13; Q17; Q18; 330; livestock; international trade; exports; meat